Implementasi Failure Mode and Effect Analysis Untuk Meminimalkan Produk Cacat - Agusti, Jefry Restu; harahap, Uun Novalia; Hasibuan, Yetti Meuthia (Metode : Jurnal Teknik Industri, 2025)
Currently the problems being faced by PT. XXX Medan is a biscuit defect that exceeds the standard defect limit desired by the company, namely a maximum of 5%. Based on these conditions, it is necessary to resolve the causes of biscuit defects using the Failure Mode and Effect Analysis (FMEA) method. The results of the Cause and Effect Diagram and FMEA analysis that have been carried out, it is known that the highest RPN value is 320, namely the oven temperature changes causing the biscuits to not be cooked perfectly, so it is necessary to control by checking the cooking temperature parameters on the oven machine display so that they always match the temperature. which are expected. Improvements need to be made to the SOP by establishing a system for checking the machine display every certain time during cooking so that the temperature value does not change. The response to the cause of this failure is continuous maintenance.